A call for inclusive conservation - Tallis, H.; Lubchenco, J.; DeClerck, Fabrice A.J. (Nature Publishing Group, 2014)
An age-old conflict around a seemingly simple question has resurfaced: why do we conserve nature? Contention around this issue has come and gone many times, but in the past several years we believe that it has reappeared as an increasingly acrimonious debate between, in essence, those who argue that nature should be protected for its own sake (intrinsic value)1, 2 and those who argue that we must also save nature to help ourselves (instrumental value).